Favorite recipes from Melissa Clark's kitchen : family meals, festive gatherings, and everything in-between - Clark, Melissa (Black Dog & Leventhal Publishers, 2018)
Clark has selected dishes from two of her previously published books to create an all-purpose cookbook that will satisfy any good appetite in any situation. Her recipes are simple to make, satisfying for the whole family, and always executed with a touch of attainable elegance and flair. -- adapted from jacket.